THE ROLE OF FIRE CARE COMMUNITY IN PREVENTION AND CONTROL OF FOREST AND LAND FIRES IN KARANG JOANG VILLAGE, BALIKPAPAN CITY - Nasir, Mohammad; Boer, Chandradewana; Kristiningrum, Rochadi Kristiningrum; Setiawan, Setiawan; Ibrahim, Ibrahim; Purwanti, Emi; Chaniago, Hilmi Dewa; Lillah, Alfa Rizky (Gorontalo Journal of Forestry Research, 2025)
This research is descriptive qualitative research that aims to explore and analyses the role of benefits, obstacles and involvement of Fire Care Community (MPA) formed by Regional Technical Implementation Unit (UPTD) of Balikpapan Protected Forest Management Unit (KPHL). Primary data consists of interviews, observations and documentation and secondary data comes from literature, reports or documents from related institutions, while the object of research is five MPA groups in Karang Joang Village Balikpapan City, East Kalimantan Province selected by purposive sampling and analyzed using a Likert Scale. The research shows that Fire Care Community (MPA) in Karang Joang Village. It is crucial in promoting awareness about the risks of forest fires through impactful outreach and education, fostering a shift in people’s behavior toward more eco-friendly practices. The existence of MPA provides significant benefits, such as ecosystem preservation, improved air quality, public health, as well as supporting sustainable agricultural practices that strengthen local economic welfare. Although MPAs face barriers such as limited resources and weak law enforcement, these challenges can be overcome with stronger collaboration. MPA engagement has also proven effective in reducing the frequency and scale of forest fires through regular patrols, early detection and rapid response